Do the effects of parents’ involvement in youth’s academic adjustment vary with youth’s developmental phase? A longitudinal investigation in China - Wei, Jun; Pomerantz, Eva M.; Ng, Florrie Fei-Yin; Yu, Yanhong; Wang, Mingzhu; Wang, Qian (Contemporary educational psychology, 2022)
•Roles of parents’ involvement in youth’s academic adjustment varied with school level.•Parents’ homework assistance benefited elementary but not middle or high school youth.•Parents’ academic socialization mainly benefited middle and high school youth. This research tested the idea that the role of parents’ homework assistance and academic socialization in youth’s academic adjustment is modulated by youth’s developmental phase. Chinese youth (N = 1863) in elementary, middle and high school and their parents reported on parents’ homework assistance and academic socialization, and youth reported on their academic adjustment as manifest in their beliefs, motivational orientation, and engagement twice over a year. Over time, parents’ assistance with homework generally had positive effects on youth’s academic adjustment in elementary school, but no effects or negative effects by high school. In contrast, parents’ academic socialization had positive effects, regardless of youth’s developmental phase, with these effects sometimes being stronger in middle and high school.